Analysis of the Return on Investment in Solar Collectors on the Example of a Household: The Case of Poland - Niekurzak, Mariusz; Kubińska-Jabcoń, Ewa (Frontiers in Energy Research, 2021)
Background: The growing consumption is what drives the development of unsustainable energy and material-intensive production technologies that emit large quantities of pollutants into the atmosphere, water, and land. Obtaining green energy allows reduction of the interference with the environment and, consequently, fits into a sustainable energy development strategy. In order to achieve the emission targets set by the EU for Poland, it is necessary to prioritize the development of renewable energy sources (RES) technologies within the energy sector. Methods: The purpose of the study was to present the results of the research relating to the return on investment of solar collectors for single-family houses in Poland. The research was presented on the basis of the legal conditions applicable to micro installations in the light of the amendment of the RES Act, and the impact of these amendments on the aspects of such investment was determined. Results: On the basis of the constructed economic model used to assess the return on investment of increasing the area of solar collectors, it has been shown that an operating installation will bring measurable economic benefits in the form of reduction in the amount of energy purchased annually in the amount of 6,756 kWh and environmental benefits in the form of reduction of carbon dioxide emissions to the atmosphere 2.4–3.6 Mg per year. An installation subsidized under the “My Electricity” program can reach an NPV of EUR 6,000 over 20 years at a discount rate r = 0 and assuming that the electricity is EUR 0.15/kWh. If the price rises to 0.2 EUR/kWh, the NPV will be 10,000 EUR. For the analyzed installation, the investment consisting in increasing the collector area in accordance with NPV is economically effective for the absorber area in the range of 5.6–7.6 m2 and reaches the maximum value for the absorber area of 6.6 m2, while the absorber area above 7 m2 contributes to reduce the value of the economic return on investment. The obtained results have been generalized, which allows to use them in the process of selecting the size of collector area for similar installations. Conclusion: The return on investment analysis carried out in respect of a detached house allowed to demonstrate that this project is fully justified. Furthermore, pursuant to the Renewable Energy Sources Act in force in Poland, treating a small entrepreneur as a prosumer who may generally take advantage of favorable conditions for discounting the produced energy leads to very favorable possibilities of settling electricity. Considering an entrepreneur as a prosumer who may use one-off depreciation of a solar collectors installation as a fixed asset and request for VAT refund is what makes such an investment very attractive in financial terms and makes it difficult to find a safe investment alternative characterized by such a high rate of return.